Cyprus : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2003)
This Selected Issues paper and Statistical Appendix provides a brief assessment of Cyprus's external position and its composition in an international perspective. It discusses estimates of Cyprus's external position based on partial International Investment Position data as well as on cumulative flows, and compares its level and composition with advanced Organization for Economic Cooperation and Development (OECD) economies and with other accession countries. It finds that a precise assessment of Cyprus's overall external position is hindered by the lack of data on nondebt stocks. The paper also analyzes aging and long-term fiscal sustainability in Cyprus.